Seroprevalence of visceral leishmaniasis and its associated factors among asymptomatic pastoral community of Dire District, Borena zone, Oromia Region, Ethiopia - Haile Ketema; Fitsum Weldegebreal; Abdella Gemechu; Tesfaye Gobena (Frontiers Media S.A., 2022)
Visceral leishmaniasis (VL) is a vector-borne protozoan neglected tropical disease. In some parts of Ethiopia, it is a public health problem and its main causative agent is the Leishmania donovani complex. The objective of the study was to determine the seroprevalence of VL and factors associated among the asymptomatic pastoral community of Dire District, Borena Zone, Oromia Region, Ethiopia. A community-based study was conducted among 432 pastoralist communities from June to July 2021. A systematic random sampling method was used to select households. Pretested structured questionnaires and face-to-face interviews were used to collect data. A single finger-prick blood sample was collected and tested for Leishmania donovani complex using an immune-chromatographic test (rk39-ICT). A logistic regression model was used to assess factors associated with VL infection and a p-value of < 0.05 was considered statistically significant. A total of 432 study participants were included (their mean age was 26.69) and 218 (50.5%) were females. The overall seroprevalence of VL was 33/432(7.6%) (95%CI: 5.32-15.60). Sero-prevalence was significantly associated with high family size (>5) (adjusted odds ratios (AOR) = 5.134; 95% CI: 2.032-9.748), sleeping or/and staying under acacia tree (AOR = 2.984; 95%CI = 1.074-8.288), presence of cracked house walls (AOR = 1.801; 95%CI: 1.026-4.926), presence of termite hills (AOR = 1.938; 95%CL: 1.002-7.050), availability of water points (AOR = 3.893; 95%CI: 1.034-7.426) and presence of domestic animals (AOR = 2.124; 95% CI: 2.341-5.108). It is recommended that community awareness on the transmission and prevention methods of Leishmania donovani complex and taking appropriate interventions on the identified factors play a greater role to prevent and control infection in the area. Further investigation is also needed to characterize the pathogens and risk factors and tackle the problem.